A Mathematical Model for On-Target Off-Tumor Effect of CAR-T Cells on Gliomas - Santurio, Daniela Silva; Barros, Luciana Rodrigues Carvalho (Frontiers in Systems Biology, 2022)
CAR-T cell immunotherapy is genetically reprogrammed T-lymphocytes that interact with cancer cells and activate an anti-tumor immune response. This therapy has been approved for clinical use for hematological cancers, but new challenges have emerged in the treatment of solid tumors. Some of the challenges include the heterogeneity of antigen expression found in solid tumors, including antigen-positive non-tumoral cells, the immune inhibitory molecules. expression, and CAR-T cell trafficking difficulty within the tumor microenvironment. We proposed a mathematical model to describe the "on-target" and "off-tumor" effects of CAR-T cell therapy for gliomas, and we investigated which parameters influenced the final outcome using a global sensitivity analysis. Our model highlights the dynamics of CAR-T cell therapy, tumor and healthy populations (antigen-positive glia, antigen-negative glia, and neurons), and it provides novel insight into the consequences of “on target” “off-tumor” effects, particularly, in the neuronal loss.